PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA - Rafi Irmiyanti; Fajar Nugraha; Riza Fatimah Zahrah (LPPM Universitas Bina Bangsa, 2022)
The problem in this study is the low student learning outcomes in Social Sciencess model subjects as shown by the number of students in class IV, only 21 students 70% are still below KKM 72. With these problems, through this study it is hoped that student learning outcomes will increase wit the applicaton of the model Snowball Throwing cooperative learning type to improve students social studies learning outcomes. The method used in this research is to use the Classroom Action Research (CAR) method, the data collection technique to determine the ability of teachers in planning and implementing during learning, test techniques to determine students learning outcomes or achieve the Snowball Throwing type cooperative learning model, and documentation teachnique in the form of photos of student activities during the learning process. The results of this study indicate that the application of the Snowball Throwing type cooperative learning model can improve students social studies learning outcomes in grade IV. The results showed that at 30 students in the implementation of cycle I there were 14 students (47%) who had reached KKM 72, and in the implementation of cycle II there were 27students (90%) who had reached KKM 72. It was concluded that the application of the Snowball Throwing type cooperative learning model could improve student social studies learning eoutcomes in natural resources material and its utilization in grade IV SD Negeri Cisugih, Jatiwaras District, Tasikmalaya Regency, 2020/2021 academic year